Acclimation of Chickrassia velutina Wight et Arn. Stem Cuttings to Water Stress - Kabir, M. A.; Kamaluddin, M.; Miah, M. D. (Indian Forester, 2002)
The acclimation potential of Chickrassia velutina Wight et Arn. Stem cuttings to water stress was investigated in the nursery with respect to four watering regimes: watering daily, three-day, seven-day and fifteen day intervals. Multi-plant plots, containing eight stem cuttings per plot and one single plant per polythene tube were distributed among three randomised blocks. Leaf area, plant height and dry weights of root, stem and total plant were measured. The species showed significant decrease in total plant biomass in water stressed conditions. One important acclimation mechanism was the allocation of assimilates to root growth relative to shoot. The species also acclimated to soil water stress by decreasing leaf area thereby reducing transpiration.